Neural Basis of Professional Pride in the Reaction to Uniform Wear - Hong, Yeon-Ju; Park, Sunyoung; Kyeong, Sunghyon; Kim, Jae-Jin (Frontiers in Human Neuroscience, 2019)
Professional pride is a positive emotion that includes self-reflection or evaluation and attitude toward one’s own occupational group. Uniforms can encourage the wearer to have professional pride. The current study aimed to elucidate the neural basis of professional pride using an experimental task related to the self in uniform and functional magnetic resonance imaging (fMRI). The person-adjective matching task, in which a participant or other in uniform or casual wear was presented with positive and negative words, was used for scanning fMRI. Imaging data from 21 adults who had an occupation requiring a uniform were analyzed to identify the main and interaction effects of individual (self vs. other), clothes (uniform vs. casual wear), and valence (positive vs. negative). Identified brain activities were correlated with psychological scales including the Rosenberg Self-esteem Scale and Group Environment Questionnaire. Whole brain analyses found that the interaction between individual and clothes was present in multiple regions such as the right ventrolateral prefrontal cortex, left dorsolateral prefrontal cortex, left middle and inferior temporal gyri, left posterior superior temporal sulcus, right temporoparietal junction, left lingual gyrus, left calcarine cortex, right insula, left caudate, and right putamen. In particular, activities in the right ventrolateral prefrontal cortex, left calcarine cortex, and right putamen in the self/uniform condition were positively correlated with several psychological scales. These results suggest that professional pride may be represented through multiple brain networks related to empathy, reward, and emotion regulation as well as the theory-of-mind network. The neural basis of professional pride is closely related to positive self-evaluation and group cohesion.